2016
DOI: 10.5935/1806-6690.20160074
|View full text |Cite
|
Sign up to set email alerts
|

Emergy efficiency analysis of sugarcane as a raw material for ethanol production

Abstract: In recent years, the expansion of sugarcane cultivation in Brazil and its growing importance in the Brazilian economy have been driven by a sharp increase in fuel alcohol production. This increase in fuel alcohol production was accompanied by increasing interest regarding the impacts of fuel crops in Brazil. In this study, regions of sugarcane expansion into deforested areas in the Atlantic Forest were studied by applying the emergy theory and indices. Environmental and economic inputs and the sustainability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…On the other hand, in the bagasse-AHR mixture, the renewability ratio (23.58%) is higher by 18.77% compared with that found in Ref. [74]. Nevertheless, in both cases, its use is undoubtedly lower than the use of bagasse.…”
Section: -88mentioning
confidence: 60%
“…On the other hand, in the bagasse-AHR mixture, the renewability ratio (23.58%) is higher by 18.77% compared with that found in Ref. [74]. Nevertheless, in both cases, its use is undoubtedly lower than the use of bagasse.…”
Section: -88mentioning
confidence: 60%
“…The renewable irrigated systems (S2A0, S2A1 and S2A2) had a lower environmental load compared to the conventional irrigated systems (S1A0, S1A1 and S1A2) due to the greater influx of renewable natural resources (wastewater) and also the lower influx of non-renewable resources from the economy (chemical fertilisers and electrical services). Vitória and Rodrigues (2016), in a study of the emergy efficiency of sugarcane, found that dependence on chemical fertilisers reduces the fraction of renewable energy and increases environmental degradation, resulting in a less sustainable production system, and highlighted that the use of alternative sources of fertiliser may improve sustainability and reduce the environmental load.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, there must be a large amount of power generation contained in nutrients, agricultural practices, among others, for the production of biomass (Vitoria & Rodriges, 2016;Kumar, Singh, Surekha & Kumar, 2014).…”
Section: Discussion Biomassmentioning
confidence: 99%